Slowka : ilustrowany polsko-angielski slowniczek dla najmlodszych (Warszawa : Wydawnictwa Naukowo-Techniczne, 1990)
A simple picture dictionary for young children; Polish/English. Ages 4-8.
Keywords: Picture dictionaries, Polish -- Juvenile literature; Polish language -- Dictionaries, Juvenile -- English